Management of Pelvic Fracture Urethral Injury in Pediatric Patients (Bangladesh Journal of Urology, 2022)
Purpose: Pediatric urethral surgery represents a significant surgical challenge due to smaller pelvis, decreased caliber and increased tissue fragility. This study aims to find the outcome and complications of perineal end to end anastomotic urethroplasty in the management of posterior urethral injury resulting from pelvic fracture.Methods: We performed 47 perineal bulbo-prostatic anastomotic urethroplasty for PFUIs from January, 2013 to January 2020. Mean age was 13 years with majority between 10 to 18 years (>85%). All were male patients. Two patients had history of failed anastomotic urethroplasty. Patients were selected as per selection criteria and were prepared for operation after adequate counseling. After surgical intervention patients were discharged with a supra-pubic catheter (SPC) and per urethral catheter in situ. On 22nd POD urethral catheter was removed and SPC on the next day if patient can void normally. 1st and 2nd follow up done on of 3rd and 6th month respectively following surgery. If patient voided well and Qmax>15ml/ sec; repair was defined as successful.Results: Success rate of anastomotic urethroplasty for PFUI was 91.47%. Total 4 procedures were failed including 1 urethro-cutaneous fistula and needed re-do anastomosis. We could not evaluate erectile dysfunction (ED) as many patients were unable to give appropriate information. Two patient developed incontinence which improved in subsequent follow-up.Conclusions: Anastomotic urethroplasty remains the gold standard in the management of PFUI. Operative series of pediatric urethral reconstruction usually involve small numbers. Experiences of anastomotic urethoplasty in large volume adult series reflects the higher outcome in pediatic patients.Bangladesh J. Urol. 2021; 24(1): 77-81